THE IMPACT OF INSTRUMENTAL ENRICHMENT STRATEGY ON DEVELOPING INFERENTIAL THINKING AND COGNITIVE ACHIEVEMENT FOR SOME LEARNING OUTCOMES AT TEACHING METHODS COURSE AMONG STUDENTS OF THE COLLEGE OF PHYSICAL EDUCATION AND SPORTS SCIENCES (ResearchJet Journal of Analysis and Inventions, 2022)
This research aims to identify the effect of the instrumental enrichment strategy in developing inferential thinking and cognitive achievement of some learning outcomes of teaching methods course among students of the Faculty of Physical Education. The researchers used the experimental design for its relevance to the nature of the research. The researchers divided the participants into two equal experimental and control groups with pre and post-tests. The study recruited 50 third-year students in the College of Education and Sports Sciences at Kirkuk University for the academic year (2021-2022). After conducting homogeneity and parity tests for the two research groups, the researchers proceeded to invest the strategy of instrumental enrichment in preparing (12) teaching plans within the approved college curriculum., the statistical program (SPSS) was used to data processing. Results showed that the instrumental enrichment strategy has a significant impact on the development inferential thinking and the cognitive achievement of some principles of teaching methods among students' participants under investigation. The researchers recommended to apply the instrumental enrichment strategy in teaching the educational sport course at university level. It is also recommended to obtain various models, strategies and methods, and avoiding the focusing on one method of teaching.